Magnet Ingestion in Children Management Guidelines and Prevention - Altokhais, Tariq (Frontiers in Pediatrics, 2021)
Purpose: Foreign body ingestion is common in children, and most foreign bodies pass spontaneously without causing serious injuries. Ingestion of multiple high-power magnet pieces is unique and increases the risk of morbidity and mortality. The longer the duration of ingestion, the increased likelihood of complications. Various management options have been reported, and there is no consensus on the ideal management which necessitates the need for a practical algorithm. The incidence of magnet ingestion has been increasing and directly related to the laws and recalls. The aim of this review is to provide an easy and practical pathway for management and to highlight the preventive rules of the legislations and recalls. Methods: PubMed/MEDLINE, the Cochrane Database of Systematic Reviews, and the list of references from all identified complete publications were searched for all publications in English-language for pediatric magnet ingestion. Conclusion: Practical and time-saving management pathways are recommended to minimize the risk of complications. Preventive rules and recalls are important for eliminating the availability of these hazardous magnets. Public awareness about the unique risks posed by these magnets if ingested is important.